Active Vibration Distribution through Restricted Topology and Single Node Control - Jiqiang Wang (Shock and Vibration)
Vibration distribution comprises both vibration control and harvesting. Active vibration distribution control represents a generic yet challenging problem to be addressed in many engineering applications. Current norm-optimization-based methods would require significant modification for its solutions. This paper proposes a restricted control method where a variety of results concerning active vibration distribution through restricted topology control and restricted single node control are obtained. Important issues associated with both parametric constraints and performance limit are also given considerations. A systematic design methodology is thus established for active vibration distribution through restricted controls. The theoretical results are exemplified with numerical examples providing detailed design procedures.